Frontline decision autonomy under decentralization: Evidence from health sector reform - Alan Zarychta; Krister Andersson; Thomas Bossert (PLoS ONE, 2026)
Decentralization is designed to transfer autonomy from more central to more local actors, yet studies show differences in the autonomy realized under these reforms. Drawing on the case of health sector decentralization in Honduras, we utilize the decision space approach and original data for over 600 frontline health workers in a matched sample to explain facility-level autonomy. We find that reported decision autonomy in four functional areas is slightly reduced under decentralization, reductions are most pronounced where decentralization is led by municipal governments or associations, rather than NGOs, and differences across staff types are modest. Furthermore, capacity and resources are necessary for expanded autonomy, particularly in organizing service delivery, while supportive accountability allows for increased autonomy in human resources and finances. Our research shows the importance of including frontline staff in studies of decision autonomy under decentralization and considering the distribution of autonomy across levels in hierarchical service delivery systems.